Prediction model of cutting force in micro-milling single crystal copper. (21st September 2022) - Lu, Xiaohong; Luan, Yihan; Meng, Xiangyue; Feng, Jianhui; Liang, Steven Y.
Micro-parts of single crystal copper have been widely used in the fields of precision instruments and electricity, but little research has been done on the prediction of micro-milling force for single crystal copper. The accurate prediction of micro-milling force is the basis of studying the cutting process and tool wear. Experiments of micro-milling single crystal copper are carried out. Based on the experimental results, the effects of spindle speed, feed per tooth and axial cutting depth on the micro-milling force are analysed by using control variable method and Taguchi method. Based on the orthogonal experimental results, micro-milling force prediction models of three crystal orientations of single crystal copper are established. The exponential empirical formula between cutting force and cutting parameters is built. The coefficients of the formula are estimated by least square method. The experiment shows that the biggest relative errors are 29.38%, 32.09%, 30.30%, respectively. The average relative errors are 17.15%, 17.48%, 16.84%, respectively. The experiment verifies the validity of the model and provides a basis for subsequent single crystal materials research. [Submitted 25 July 2020; Accepted 27 October 2020]